Brazilian Jiu-Jitsu Simulated Competition Part II: Physical Performance, Time-Motion, Technical-Tactical Analyses, and Perceptual Responses - Andreato L.V.* (2015)
© 2015 National Strength and Conditioning Association.The aim of this study was to analyze performance, time structure, technical actions, and perceptual responses in Brazilian jiu-jitsu athletes during a simulated competition. For this purpose, 10 athletes were analyzed in a simulated competition (4 matches of 10 minutes). Physical tests and scales of the perception of effort and recovery were applied. The matches were recorded for the purpose of technical-tactical analysis and to determine the time structure. The main results show that in the simulated competition, reaction time (F 2.5,17.6 2.7; p 0.087; η 2 0.28) and flexibility (F 7,63 1.5; p 0.172; η 2 0.15) were unchanged across the matches. An analysis of variance showed a significant difference for grip endurance using the kimono (F 2.0,15.9 8.1; p 0.004; η 2 0.50), which was not confirmed by the Bonferroni test. Jump height indicated postactivation potentiation after match 2 (F 7,63 3.5; p 0.003; η 2 0.28). The maximal isometric handgrip strength in the dominant hand (F 3.2,28.6 2.9; p 0.049; η 2 0.24) and in the nondominant hand (F 7,63 3.8; p 0.002; η 2 0.30) showed a decline after matches 3 and 4. Although these data indicate the onset of fatigue, the effort/pause ratio of the matches was not altered (F 3,12 0.6; p 0.624; η 2 0.13). The perceptions of effort (F 3,27 0.9; p 0.469; η 2 0.09) and recovery (F 1.9,17.0 2.4; p 0.125; η 2 0.21) and the degree of fatigue reported (F 1.5,13.8 0.5; p 0.588; η 2 0.05) did not change during the simulated competition. Thus, it may be concluded that the execution of successive matches causes a decline in maximal isometric handgrip strength. No changes in the time structure of the matches or in the perceptual responses were observed.